Set the prairie on fire: an autoethnographic confrontation of colonial entanglements - RedCorn, Sean Alexander (Kansas State University, 2017)
There is minimal scholarship related to modern Osage perspectives in the field of education. Yet, the pursuit of cultural healing relies on self-representation to move Osages toward a higher degree of self-determination, and calls for voices within the community who share zones of cultural and professional intersectionality. Using Red Pedagogy (Grande, 2008) and traditional Osage ribbon work (Dennison, 2012, 2013) as a framework, this critical Indigenous autoethnographic inquiry works to advance conversations about settler-colonial entanglements in education from the perspective of an Indigenous (Osage)-White educator and educational leadership doctoral student. This inquiry uses writing as both field and method (Richardson & St. Pierre, 2005) to explore Osage perspectives related to topics of Transformational Indigenous Praxis (Pewewardy, 2017), White privilege (McIntosh, 2003) as a pale-skinned American Indian, American Indian mascots (Pewewardy, 2000) from educational leadership perspectives (NPBEA, 2015; Waters & Cameron, 2007), and ecologically informed consciousness (Cajete, 1994).
Keywords: American Indian education; Indigenous autoethnography; White privilege; Red Pedagogy; Osage; Transformational Indigenous Praxis